Single-cell sequencing provides clues about the host interactions of segmented filamentous bacteria (SFB) - Pamp, Sünje J.; Harrington, Eoghan D.; Quake, Stephen R.; Relman, David A.; Blainey, Paul C. (Genome Research, 2012)
Segmented filamentous bacteria (SFB) are host-specific intestinal symbionts that comprise a distinct clade within the Clostridiaceae, designated Candidatus Arthromitus. SFB display a unique life cycle within the host, involving differentiation into multiple cell types. The latter include filaments that attach intimately to intestinal epithelial cells, and from which “holdfasts” and spores develop. SFB induce a multifaceted immune response, leading to host protection from intestinal pathogens. Cultivation resistance has hindered characterization of these enigmatic bacteria. In the present study, we isolated five SFB filaments from a mouse using a microfluidic device equipped with laser tweezers, generated genome sequences from each, and compared these sequences with each other, as well as to recently published SFB genome sequences. Based on the resulting analyses, SFB appear to be dependent on the host for a variety of essential nutrients. SFB have a relatively high abundance of predicted proteins devoted to cell cycle control and to envelope biogenesis, and have a group of SFB-specific autolysins and a dynamin-like protein. Among the five filament genomes, an average of 8.6% of predicted proteins were novel, including a family of secreted SFB-specific proteins. Four ADP-ribosyltransferase (ADPRT) sequence types, and a myosin-cross-reactive antigen (MCRA) protein were discovered; we hypothesize that they are involved in modulation of host responses. The presence of polymorphisms among mouse SFB genomes suggests the evolution of distinct SFB lineages. Overall, our results reveal several aspects of SFB adaptation to the mammalian intestinal tract.